(untitled) (Medico Legal Update, 2020)
Hepatitis an infection in the liver is very contagious and is caused by the hepatitis virus. Objectives: The study aims to evaluate nurses performance concerning infection control practices, and to determine the relationship between nurses performance and their demographic characteristics. As well as, to determine the relationship between nurses performance and patients clinical data. A quantitative descriptive design was conducted in Hilla City Hospital for the period of from September 2018 to March 2019. A checklist was used as a means of data collection from those who works at Hemodialysis unit. Non probability sampling (purposive) has been performed on (30) nurses and (30) patients in dialysis unit. direct observation as mean of data collection. Nurses were observed three times while they are working in the dialysis unit. The data were analyzed through the application of descriptive and inferential data analysis. The study results reveals that (80%) sometime applied hand washing, (76.7%) were sometime apply uniform, and (66.7%) were always apply gloves, (53.3%) never wearing gown, and (86.7%) never wearing mask. A majority of (63.3%) of nurses were partially performed infection control measures. There is insignificant association with nurses demographic characteristics at p-value >0.05.Hepatitis an infection in the liver is very contagious and is caused by the hepatitis virus. Objectives: The study aims to evaluate nurses performance concerning infection control practices, and to determine the relationship between nurses performance and their demographic characteristics. As well as, to determine the relationship between nurses performance and patients clinical data. A quantitative descriptive design was conducted in Hilla City Hospital for the period of from September 2018 to March 2019. A checklist was used as a means of data collection from those who works at Hemodialysis unit. Non probability sampling (purposive) has been performed on (30) nurses and (30) patients in dialysis unit. direct observation as mean of data collection. Nurses were observed three times while they are working in the dialysis unit. The data were analyzed through the application of descriptive and inferential data analysis. The study results reveals that (80%) sometime applied hand washing, (76.7%) were sometime apply uniform, and (66.7%) were always apply gloves, (53.3%) never wearing gown, and (86.7%) never wearing mask. A majority of (63.3%) of nurses were partially performed infection control measures. There is insignificant association with nurses demographic characteristics at p-value >0.05.